1999
DOI: 10.1046/j.1365-2141.1999.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte autoantibodies in paediatric patients with sickle cell disease receiving transfusion therapy: frequency, characteristics and significance

Abstract: The formation of erythrocyte autoantibodies following transfusion therapy has been described in case reports and small series. To determine the frequency, serological characteristics, and clinical significance of this phenomenon in paediatric patients with sickle cell disease, we analysed the patient database at the Duke University Pediatric Hematology Clinic. We identified children who received multiple erythrocyte transfusions, then reviewed clinical records to identify children who developed erythrocyte aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 48 publications
3
83
0
3
Order By: Relevance
“…It was also suggested that alloantibody binding to the RBCs could lead to conformational changes of the antigenic epitope that ultimately stimulates production of autoantibodies [42]. It is possible that certain people are genetic responders who have an increased tendency to develop RBC autoantibodies and the tendency toward autoantibody formation could reflect an overall dysfunction of the immune system [43].In study by Ahmed there was a significant association of splenectomy with alloimmunization and auto antibodies (P = 0.03, 0.001 respectively).Wiener et al [44], demonstrated significant elevations in RBC bound IgG in thalassaemia patients which was more abundant in splenectomized than nonsplenectomized subjects. They found that the absence of a spleen may further enhance the immune response to the infused foreign antigens which are not effectively filtered.…”
Section: Other Factorsmentioning
confidence: 99%
“…It was also suggested that alloantibody binding to the RBCs could lead to conformational changes of the antigenic epitope that ultimately stimulates production of autoantibodies [42]. It is possible that certain people are genetic responders who have an increased tendency to develop RBC autoantibodies and the tendency toward autoantibody formation could reflect an overall dysfunction of the immune system [43].In study by Ahmed there was a significant association of splenectomy with alloimmunization and auto antibodies (P = 0.03, 0.001 respectively).Wiener et al [44], demonstrated significant elevations in RBC bound IgG in thalassaemia patients which was more abundant in splenectomized than nonsplenectomized subjects. They found that the absence of a spleen may further enhance the immune response to the infused foreign antigens which are not effectively filtered.…”
Section: Other Factorsmentioning
confidence: 99%
“…59 In the STOP I trial, matching for the C, E, and K antigens decreased the rate of alloimmunization by a factor of 6 per unit of exposure. 60 Although extensive blood type matching can be challenging, blood transfusions containing antigens to which the donor is alloimmunized not only increases the risk of hemolytic reactions but also shortens the half-life of the infused RBCs 61 ; consequently, additional transfusions are required to maintain a low HbS, which further increases the risk of iron overload, infection, and alloimmunization.…”
Section: Extended Blood Typingmentioning
confidence: 99%
“…9 Patients presenting at the age 1 or 2 years of life were transfusion dependent for life. 10 Majority of our patients started on transfusions between the ages of 3month to 1 year old. One patient started transfusion at the age of 1month, while one patient started transfusion at 3years old.…”
Section: Efficacy Of Transfusion Regimementioning
confidence: 99%